1975
DOI: 10.1139/y75-131
|View full text |Cite
|
Sign up to set email alerts
|

Absence of 'Superfast' Axonal Transport in Rat Sciatic Nerve

Abstract: Axonal transport of labelled protein was studied in rat sciatic nerve by analyzing nerve segments at intervals after injection of L-[3H]leucine into the lumbar spinal cord. Some nerves were sectioned before injection so that material in transit accumulated proximal to the section. The segments distal to the section served as controls for incorporation into the nerve of blood-borne label. An analysis of TCA-soluble and TCA-insoluble activity in cut and intact nerve segments was also made. No evidence was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1976
1976
1981
1981

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…of relative accumulation (n 2 lo), and horizonta1 dimensions of the 3 h accumulation period. A; motor axons, proximal crush: B; sensory axons, proximal crush: C; motor axons, distal crush: D; sensory axons, distal crush.viously severed from the spinal column, showing that all TCA-soluble activity is blood-born(BISBY, 1975). Electrophoresis of charged proteins to the crush sites is eliminated as a major source of accumulated activity because injury potentials decline exponentially with time, while accumulation of labelled protein increases linearly with time(BISBY, 1975).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…of relative accumulation (n 2 lo), and horizonta1 dimensions of the 3 h accumulation period. A; motor axons, proximal crush: B; sensory axons, proximal crush: C; motor axons, distal crush: D; sensory axons, distal crush.viously severed from the spinal column, showing that all TCA-soluble activity is blood-born(BISBY, 1975). Electrophoresis of charged proteins to the crush sites is eliminated as a major source of accumulated activity because injury potentials decline exponentially with time, while accumulation of labelled protein increases linearly with time(BISBY, 1975).…”
mentioning
confidence: 99%
“…A; motor axons, proximal crush: B; sensory axons, proximal crush: C; motor axons, distal crush: D; sensory axons, distal crush.viously severed from the spinal column, showing that all TCA-soluble activity is blood-born(BISBY, 1975). Electrophoresis of charged proteins to the crush sites is eliminated as a major source of accumulated activity because injury potentials decline exponentially with time, while accumulation of labelled protein increases linearly with time(BISBY, 1975). It is concluded that the accumulations are a measure of axonal transport, proximal accumulations representing orthograde transport, distal accumulations representing retrograde transport.…”
mentioning
confidence: 99%
“…This idea was supported by the results of Tang et al (1974) who found that [3'P]~rthophosphate-labelled material travelled at 120 mm/24 h in the mouse sciatic nerve. These workers also described material moving at 850 mm/ day in the same preparation but some doubt has been subsequently cast on the validity of the finding of a "super fast" transport (Bisby 1975). These findings in which "P appeared to be transported at some rapid velocity, albeit not a velocity identical with that obtained with protein precursors, were not supported at all by the early findings of Ochs and Ranish (1969).…”
Section: The Form Of the Transported Materialsmentioning
confidence: 99%